Before Dorothy - Gaynor, Hazel (New York : Berkley, 2025)
"Chicago, 1924: Emily Gale and her new husband, Henry, yearn to leave the bustle of Chicago behind for the promise of their own American dream. But leaving the city means leaving Emily's beloved sister, Annie, who was once closer to her than anyone in the world. Kansas, 1932: Emily and Henry have made a life in the warmth of the community of Liberal, Kansas, and among the harsh beauty of the prairie. Their lives hold a precarious and hopeful purpose, until tragedy strikes and their orphaned niece, Dorothy, lands on their doorstep. The wide-eyed child isn't the only thing to disrupt Emily's world. Drought and devastating dust storms threaten to destroy everything, and their much-loved home becomes a place of uncertainty and danger. When the past catches up with the present and old secrets are exposed, Emily fears she will lose the most cherished thing of all: Dorothy."--.
new book 2025 summer.
Keywords: Sisters; History; Depressions; Prairies; Dust storms; Orphans; Aunts; Secrecy; Nieces; Novels